Antioxidants and Vasodilators for the Treatment of Noise-Induced Hearing Loss: Are They Really Effective? - Alvarado, Juan Carlos; Fuentes-Santamaría, Verónica; Juiz, José M. (Frontiers in Cellular Neuroscience, 2020)
We live in a world continuously immersed in noise, an environmental, recreational and occupational factor present in almost every daily human activity. Exposure to high-level noise could affect the auditory function of individuals at any age, resulting in a condition called noise-induced hearing loss (NIHL). Given that by 2018, more than 400 million people worldwide were suffering from disabling hearing loss and that about one-third involved noise over-exposure, which represents more than 100 million people, this hearing impairment represents a serious health problem. As of today, there are no therapeutic measures available to treat NIHL. Conventional preventive measures, including public awareness and education and physical barriers to noise, do not seem to suffice, as the population is still being affected by damaging noise levels. Therefore, it is necessary to develop or test pharmacological agents that may prevent and/or diminish the impact of noise on hearing. Data availability about the pathophysiological processes involved in triggering NIHL has allowed researchers to use compounds, that could act as effective therapies, by targeting specific mechanisms such as excess generation of free radicals and blood flow restriction to the cochlea. In this review, we summarize the advantages/disadvantages of these therapeutic agents, providing a critical view on whether they could be effective in the human clinic.